Are We Confusing Poverty with Preferences? - van den Boom, Bart; Halsema, Alex; Molini, Vasco (World Bank, Washington, DC, 2015)
Modifying the national poverty line to the context of observed consumption patterns of the poor is becoming popular. A context-specific poverty line would be more consistent with preferences. This paper provides theoretical and empirical evidence that the contrary holds and that the national poverty line is more appropriate for comparing living standards among the poor, at least under prevailing conditions in Mozambique and Ghana. The problem lies in the risk of downscaling the burden associated with cheap-calorie diets and the low nonfood component of the rural poor. The paper illustrates how observed behavior may neither reveal preferences nor detect heterogeneous preferences among the poor. Rather, the consumption pattern is the upshot of the poverty condition itself. Poverty is confused with preferences if observed cheap-calorie diets are seen as a matter of taste, whereas in fact they reflect a lack of means to consume a preferred diet of higher quality, as food Engel curve estimates indicate. Likewise, a smaller nonfood component is not a matter of a particular distaste, but an adaptation to the fact that various nonfood items (such as transport) and basic services (such as electricity and health) are simply absent in rural areas.